Cognitive test anxiety and cognitive enhancement: the influence of students’ worries on their use of performance-enhancing drugs - Sattler, Sebastian (Substance use & misuse, 2013)
This online panel study (nt1 = 5,882; nt2 = 3,486 (randomly selected)) used multiple metrics to assess the prevalence of the nonmedical use of prescription medication for enhancing cognitive performance among German university students in 2010. Rare events logistic regression revealed that increased cognitive test anxiety increased the prevalence of medication use over various time windows. Negative binomial regression models showed that the higher the cognitive test anxiety, the higher the use frequencies were during the previous six months. The models controlled for expected side effects, risk attitudes, self-attributed competencies, prior medication use, sex, and age. We also discuss the study's implications.